THE EFFECT OF THE COOPERATIVE LEARNING MODEL TYPE PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW (PQ4R) ON STUDENTS' CRITICAL THINKING SKILLS ON THE CIRCLE - Waluya, Stevanus Budi; Diyanti, Nur; Novianti, Dwi Erna; Suriyah, Puput; Mariana, Dina; Puspitaningsih, Siska (Journal of Technology, Mathematics and Social Science, 2023)
Abstract: The learning model used by the teacher affects the learning outcomes to be achieved. The PQ4R-type cooperative learning model was expected to improve students' critical thinking skills. This study aims to determine the effect of cooperative learning model type Preview, Question, Read, Reflect, Recite, Review (PQ4R) on students' critical thinking skills on the subject of the circle of class VIII even semester MTs Tarbiyatul Islam Soko in 2017/2018 academic year. The type of research used in this research is quasi-experimental design (pseudo-experimental). The population in the study were all students of grade VIII MTs Tarbiyatul Islam Soko in the 2017/2018 academic year. The samples used in the study were students of class VIII B as the control class and students of class VIII D as the experimental class. The research instruments in this study were observation sheets and test questions on students' critical thinking skills. The data analysis technique used was a statistical technique with t-test and prerequisite test analysis with Lilliefors test for normality test, Bartlett test for homogeneity test, and t-test for a balance test. The results showed that learning with a cooperative learning model type Preview, Question, Read, Recite, Reflect, Review (PQ4R) has a better influence on students' critical thinking skills. This can be seen from the magnitude of       that        is -6.134 > 2.2906. The average of the last test also showed that the experimental class had better critical thinking skills than the control class, which was 81 for the experimental class and 70 for the control class. Based on the observation results on the application of the PQ4R type cooperative learning model in the experimental class at MTs Tarbiyatul Islam Soko, the average student learning activity is in the good category in each indicator, namely 75.69%; 72.74%; 70.65%; 74.65%; 73.09%; and 74.39%. Keywords: PQ4R type Cooperative Learning Model; Students' Critical Thinking Ability